Governing seed for food production: The international treaty on plant genetic resources for food and agriculture - Nina Isabella Moeller (South Centre, 2021)
Plant genetic resources for food and agriculture (PGRFA) are part of the foundation of agriculture and of central importance to food sovereignty. These gain an increasingly pivotal role in the context of climate crises, which are threatening predictable crop production, and the erosion of agricultural biodiversity. The main instrument for the governance of PGRFA is the International Treaty on Plant Genetic Resources for Food and Agriculture. Strengthening the Treaty is crucial. The Treaty establishes a binding international framework for the conservation and sustainable use of plant genetic resources for food and agriculture, and the fair and equitable sharing of the benefits arising from their use. Since 2013, negotiations have been underway to enhance the functioning of the Multilateral System of Access and Benefit-sharing. Current informal consultations may pave the way for constructive negotiations at the next Governing Body meeting in May 2022.
Keywords: 300